2019
DOI: 10.1101/511907
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic Development of Sandwich Immunoassays for the Plasma Secretome

Abstract: The plasma proteome offers a clinically useful window into human health and disease. With recent progress made on the development of highly multiplexed immunoassays with high sample throughput, a remaining need is to establish a pipeline for validating the individual proteins that build such bio-signatures by using targeted assays. In order to streamline such efforts, we developed a workflow to build dual binder sandwich immunoassays (SIA) and chose to evaluate this on proteins predicted to be secreted form ce… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…To ensure that the antibodies HPA023138 and HPA022845 captured neurofilament medium polypeptide (NF-M) in the studied sample material, a sandwich assay directed toward NF-M was developed according to a previously published workflow [28] (see Supplementary Materials and Methods).…”
Section: Validation Of Nf-m Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure that the antibodies HPA023138 and HPA022845 captured neurofilament medium polypeptide (NF-M) in the studied sample material, a sandwich assay directed toward NF-M was developed according to a previously published workflow [28] (see Supplementary Materials and Methods).…”
Section: Validation Of Nf-m Antibodiesmentioning
confidence: 99%
“…The semi-quantitative nature of the SBA assay could be viewed as a limitation since no definite concentrations are obtained. However, it has previously been shown that the protein levels acquired by the use of suspension bead arrays can be reproduced using other methods [28,52,66,67].…”
Section: Both Principal Component Analysis and Analysis Of Singlementioning
confidence: 99%